دراسة أثرية فنية تحليلية مقارنة لمصحف إيراني محفوظ بجامعة أم القرى بمكة المكرمة An Artistic Archaeological and Analysis Comparative Study of Holy Iranian Muṣḥaf Manuscript Preserved in Umm Al-Qura University/Mecc - Samira E. Almnoawty (Journal of General Union of Arab Archaeologists, 2024)
الملخص: يتناول هذا البحث دراسة أثرية فنية تحليلية مقارنة لمخطوط مصحفى غير مؤرخ محفوظ بجامعة أم القري بمكة المكرمة رقم سجل:(3649. Nº)، حيث يحتوى المخطوط المصحفى فقط على اسم محمد هاشم من ضمن النقوش الكتابية المنفذة على حاشية غلاف المخطوط، استطاعت الباحثة من خلال الدراسة الوصفية التسجيلية والتحليلية المقارنة أن تؤرخ المخطوط المصحفى إلى أواخر القرن الثانى عشر وبداية القرن الثالث عشر الهجرى / أواخر القرن الثامن عشر وبداية القرن التاسع عشر الميلادى أى بالعصر القاجارى: [1193-1345ه/ 1779-1926م] وذلك من خلال السمات والخصائص الفنية للمدرسة الإيرانية فى التجليد فى العصر القاجارى، والتعرف على شخصية الخطاط والمذهب وهو: محمد هاشم ابن محمد صالح اللؤلوئ الأصفهانى صاحب مدرسة خط النسخ فى إيران فى العصر القاجارى بعد إحيائه على يد الخطاط أحمد النيريزى فى القرن الثانى عشر هجرى/ الثامن عشر ميلادي، مع رصد أعمال الخطاط الفنية والعوامل المؤثرة على المخطوط. Abstract: This research sheds light on the Holy Iranian muṣḥaf manuscript preserved in Umm Al-Qura University/Mecca Nº.3649. The calligrapher did not mention the date of the script, but he mentioned only his name, Muhammad Hashim, within the inscriptions on the oil cover" Lacquer". The researcher could date the manuscript through archaeological and artistic analysis studies to the end of the 12-13 H.D. century or 18-19 A.D. century through the artistic features of the Iranian school of binding in the Qajar era. In addition, the researcher has to identify the calligrapher responsible for writing the Holy Iranian muṣḥaf manuscript. Based on artistic features of his works and comparative analysis, he is Muhammad Hashim ibn Mohammad Saleh al-Alou'i al-Sfahny. Muhammad Hashim revived Naskh calligraphy after the calligrapher Ahmed Al-Nayrizi in 12 H.D. century/18A.D. In addition, the researcher gives a short biography to the calligrapher and examines the influence of various factors on the manuscript.